Creating a virtual equity, diversity, and inclusion community of practice - Khwaja, Tehmina; Wager, Amanda; Lyon, Melissa; O’Neil Green, Denise (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2023)
Post-secondary institutions in Canada are trying to bring about policy and culture change to promote equity, diversity, and inclusion (EDI) on their campuses. Uniquely, smaller institutions face barriers due to lack of capacity and personnel. As such, the research presented in this note from the field recommends that forming virtual communities of practice to learn EDI best practices from similar institutions can aid in building capacity and addressing those barriers. However, for EDI communities of practice to be sustainable, the folks leading the community have to be in ongoing, empowered EDI positions rather than being precarious contract employees, as is often the case at smaller Canadian institutions.